Construction and Standardisation of Agripreneurial Performance Scale - Purabi,; Kalyan Ghadei,; J Nikhil,; M. Chennamadhava,; Krishnamayee Sethi,; Rohan Prasad Gupta, (Indian Journal of Extension Education, 2024)
One of the most vital factors in making agriculture successful is the promotion of agripreneurship among farmers in our country. With growing demand of the food and the scope of agripreneurship in the entrepreneurial pyramid makes it more attractive. To develop and validate the agripreneurial performance scale, 94 statements were selected including financial and non-financial measures of agripreneurial performance by going through various scientific literatures, again those statements were screened based on 14 point criteria suggested by Edward (1957) during 2023. 69 statements were selected and sent to 80 judges. Based on judgments of 30 judges, statements were subjected to item analysis, after calculation of t value 40 statements were finalised and included in the final scale. Reliability was calculated using split half method, reliability coefficient value was 0.81 which was further verified by Spearman’s Brown formula and the value was found 0.89, which implies the scale is reliable. The Cronbach alfa value of 0.83 refers to the high consistency of the developed scale. Validity was ensured with the help of content validity. The final scale was developed including 40 statements that reflect new ideas.